Effect of nucleating agents on the strain-induced crystallization of poly(l-lactide). (18th May 2015) - Yin, Yongai; Zhang, Xiuqin; Song, Yan; de Vos, Sicco; Wang, Ruyin; Joziasse, Cornelis A.P.; Liu, Guoming; Wang, Dujin
Abstract: This work examined the effect of nucleating agents on the strain-induced crystallization of poly(l -lactide) (PLLA). Talc and poly(d -lactide) (PDLA) were used as the nucleating agents of PLLA. Wide angle X-ray scattering (WAXS) revealed that the original injection molded specimens of nucleated PLLA blends were free of PLLA α crystal. The structural evolution during uniaxial stretching of neat and nucleated PLLA above the glass transition temperature was investigated by in-situ WAXS. It was observed that the nucleating agents significantly accelerated the crystallization of PLLA during stretching. The accelerating effect for the PLLA crystallization during stretching increased in the following order: PDLA/talc > PDLA > talc. In step-strain measurements with a high stretching speed, the effect of nucleating agents on the crystallization of PLLA showed a strain-dependence. The enhancement of crystallization by nucleating agents was remarkable at 200% strain. However, with 500% strain, the strain-induced crystallization was dominant and the effect of nucleating agents on crystallization of PLLA was not obvious. The results were analyzed considering the nucleating effect of nucleating agents on PLLA. Graphical abstract: Highlights: The structural evolution during uniaxial stretching of neat and nucleated PLLA above Tg was investigated by in-situ WAXS. The nucleating effect for PLLA crystallization increased in the following order: PDLA/talc > PDLA > talc. In step-strain measurements, the effect of nucleating agent on the crystallization of PLLA showed a strain-dependence.